Motility increase of adherent invasive Escherichia coli (AIEC) induced by a sub-inhibitory concentration of recombinant endolysin LysPA90 - Hwang, Yoon Jung; Jo, Jaehak; Kim, Eunsuk; Yoon, Hyunjin; Hong, Hyewon; Kim, Min Soo; Myung, Heejoon (Frontiers in Microbiology, 2022)
Endolysins are bacteriophage enzymes required for the eruption of phages from inside host bacteria via the degradation of the peptidoglycan cell wall. Recombinant endolysins are increasingly being seen as potential antibacterial candidates, with a number currently undergoing clinical trials. Bacteriophage PBPA90 infecting Pseudomonas aeruginosa harbors a gene encoding an endolysin, lysPA90. Herein, recombinant LysPA90 demonstrated an intrinsic antibacterial activity against Escherichia coli in vitro. It was observed that a sub-inhibitory concentration of the recombinant protein induced the upregulation of genes related to flagella biosynthesis in a commensal E. coli strain. Increases in the number of bacterial flagella, and in motility, were experimentally substantiated. The treatment caused membrane stress, leading to the upregulation of genes rpoE, rpoH, dnaK, dnaJ, and flhC, which are upstream regulators of flagella biosynthesis. When adherent invasive Escherichia coli (AIEC) strains were treated with subinhibitory concentrations of the endolysin, bacterial adhesion and invasion into intestinal epithelial Caco-2 cells was seen to visibly increase under microscopic examination. Bacterial counting further corroborated this adhesion and invasion of AIEC strains into Caco-2 cells, with a resultant slight decrease in the viability of Caco-2 cells then being observed. Additionally, genes related to flagella expression were also upregulated in the AIEC strains. Finally, the enhanced expression of the proinflammatory cytokine genes TNF-, IL-6, IL-8, and MCP1 in Caco-2 cells was noted after the increased invasion of the AIEC strains. While novel treatments involving endolysins offer great promise, these results highlight the need for the further exploration of possible unanticipated and unintended effects.